Valle-Inclán, Ramón María del (2023 [1920]): "Flor de Santidad. Historia Milenaria. La escribió Don Ramón del Valle Inclán". Opera Omnia, Vol. II. Santiago de Compostela: Editora Alvarellos, 252 pp. - del Valle-Inclán Alsina , Joaquín; Rodríguez Tudela, Olivia (Madrygal. Revista de Estudios Gallegos, 2023)
Review of Flor de Santidad. Historia Milenaria. La escribió Don Ramón del Valle Inclán. Opera Omnia, Vol. II (Santiago de Compostela: Editora Alvarellos, 2023; facsimile reproduction of the 1920 edition; original illustrations by José Moya del Pino [1920]; prologue by Joaquín del Valle-Inclán Alsina; introduction by Olivia Rodríguez-Tudela), by Antonio Arroyo Almaraz.